Analysis socio-spatial segregation by the index of social exclusion: the case of Ulaanbaatar city - Yondon, Undral (Studia Philosophiae Et Juris, 2024)
The aim of the paper is to analyze spatial segregation using the method of social exclusion index and explain its results. Spatial separation was first developed by Chicago School students using the example of an American city and developed a approach to urban ecology. According to this concept, urban residents tend to live in clusters due to certain characteristics. Some researchers in Mongolia have studied and published studies of this phenomenon. The most interesting research is the World Bank's Urban Poverty Programme. According to the results of the study, the Kharoos were released in 2016 where multidimensional poverty clustered in the capital. The lowest poverty regions are mainly located in central cities, and the deepest poverty regions are Songino-Hazar Khan, Benassurk, and Khan-Uul. We examined spatial segregation in the capital with the help of social exclusion indexes. The index includes 12 indicators, including the economic situation of households, working conditions, people's ability to save and increase human capital, consumption and leisure time. In central cities, exclusion is relatively low, but increases closer to suburbs. At the same time, the level of education of residents and the number of people who are regularly employed increases as they approach the city centre. Хотын сегрегцаийг нийгмийн тусгаарлагдмал байдлын индексээр шинжлэх нь: Улаанбаатар хотын жишээн дээр Хураангуй: Энэхүү өгүүлэлд нийслэл хотын хөгжлийг тооцох 86 бүлэг үзүүлэлт бүхий индексийн нэг үзүүлэлт болох улсын эрүүл мэндийн байгууллагын тусламж, үйлчилгээний чанарын индексийг тооцоход ашигласан арга зүй, судалгааны үр дүнг танилцуулна. Улсын эрүүл мэндийн тусламж, үйлчилгээний чанарын индексийг улсын эрүүл мэндийн тусламж, үйлчилгээний хүртээмжийн дэд индекс, эрүүл мэндийн даатгалд хамрагдалтын дэд индекс, эрүүл мэндийн даатгалын ашиглалтын дэд индекс, улсын эрүүл мэндийн үйлчилгээний шуурхай байдлын дэд индекс, улсын эрүүл мэндийн байгууллагын боловсон хүчний бэлэн байдлын дэд индекс, эрүүл мэндийн тусламж үйлчилгээний бэлэн байдлын дэд индекс, эрүүл мэндийн байгууллагын тохижилт, тоног төхөөрөмжийн бэлэн байдлын индекс, улсын эрүүл мэндийн байгууллагын тусламж үйлчилгээний чанарын индекс, эмчилгээний үр дүн дэх сэтгэл ханамжийн үнэлгээний дэд индекс гэсэн 9 дэд индексээр тооцсон. Судалгааны дүнгээр дэд индекс бүрийн үзүүлэлт харилцан адилгүй нэлээд зөрүүтэй байх бөгөөд Улаанбаатар хотын улсын эрүүл мэндийн байгууллагын тусламж, үйлчилгээний чанарын нэгдсэн индекс хувийн эрүүл мэндийн байгууллагын тусламж, үйлчилгээний чанарын индекс болон нийслэлийн эрүүл мэндийн байгууллагын тусламж үйлчилгээний нэгдсэн индексээс доогуур байв. Tүлхүүр үгс: нийслэл, эрүүл мэнд, эрүүл мэндийн даатгал, бэлэн байдал, эрүүл мэндийн байгууллага